Krüppel-like factor 15 in liver diseases: Insights into metabolic reprogramming - Hao Chen; Hao Chen; Lan-Lan Li; Lan-Lan Li; Yan Du; Yan Du (Frontiers Media S.A., 2023)
Liver diseases, characterized by metabolic disorder, have become a global public health problem with high morbidity and mortality. Krüppel-like factor 15 (KLF15) is a zinc-finger transcription factor mainly enriched in liver. Increasing evidence suggests that hepatic KLF15 is activated rapidly during fasting, and contributes to the regulation of gluconeogenesis, lipid, amino acid catabolism, bile acids, endobiotic and xenobiotic metabolism. This review summarizes the latest advances of KLF15 in metabolic reprogramming, and explore the function of KLF15 in acute liver injury, hepatitis B virus, and autoimmune hepatitis. which aims to evaluate the potential of KLF15 as a therapeutic target and prognostic biomarker for liver diseases.